A Novel Prognostic Scoring System Integrating Gene Expressions and Clinicopathological Characteristics to Predict Very Early Relapse in Node-Negative Estrogen Receptor-Positive/HER2-Negative Breast Cancer - Lin, Caijin; Wu, Jiayi; Lin, Lin; Fei, Xiaochun; Chen, Xiaosong; Huang, Ou; He, Jianrong; Chen, Weiguo; Li, Yafen; Shen, Kunwei; Zhu, Li (Frontiers in Oncology, 2020)
Background: Despite low aggressiveness in tumor biology and high responsiveness to endocrine therapy, subgroups of patients with estrogen receptor-positive/HER2-negative (ER+/HER2-) breast cancer relapse early in the first two years after initiation of endocrine therapy, indicating potential endocrine resistance. Accordingly, we attempted to establish a scoring system to inform the first-two-year prognosis (F2P Score). Methods: Patients with node-negative ER+/HER2- breast cancer and complete data of gene expressions in 21-gene panel were retrospectively retrieved from Shanghai Jiao Tong University Breast Cancer Database (SJTU-BCDB). The F2P Score was established based on the clinical and genomic variables associated with first-two-year relapse after shrinkage correction and validated using bootstrap resampling method. Model performance was quantified by Harrell’s concordance-index (C-index) and Bayesian information criteria (BIC). Results: F2P Score was established by integrating the clinical (age and tumor size) and genomic (ESR1, PGR, BCL2, CD68, GSTM1, and BAG1) variables with C-index of 0.71 and BIC of 397.46. Bootstrap C-index was 0.72 (95%CI, 0.62-0.81) and BIC was 396.75 (95%CI, 252.37-541.13). A higher score indicated increased likelihood of first-two-year relapse when used as continuous (HR, 2.94; 95%CI, 1.87-4.61) or categorical (HR, 3.68; 95% CI, 1.70-8.00) predictors in multivariate analysis. Both continuous and categorical F2P Score also remained prognostic for overall survival and other endpoints. No significant interaction was observed between F2P Score and treatment subgroups. Additionally, F2P Score outperformed IHC4, clinical treatment score and 21-gene test in predicting first-two-year relapse. Conclusion: The F2P Score reported herein, integrating the clinicopathological and genomic variables, may inform prognosis and endocrine responsiveness. Treatment escalation may be an alternative strategy after tradeoffs of benefits and risks for patients with higher score.